Role of 2D Strain in the Early Identification of Cardiac Dysfunction and in the Risk Stratification of Arteriogenic Erectile Dysfunction Patients. Issue 8 (1st August 2016) - Zehir, Regayip; Karabay, Can Yucel; Kocabay, Gonenc; Erdem, Mehmet Remzi; Balaban, Muhsin; Kirma, Cevat
ABSTRACT: Background: Vasculogenic erectile dysfunction is a harbinger of vascular disease. Comprehensive cardiac workup is accepted to be beneficial in men with this condition, especially those with otherwise unrecognized cardiovascular disease. We aimed to evaluate the role of two-dimensional speckle-tracking echocardiography (2D-STE) for noninvasive evaluation in patients with documented arteriogenic erectile dysfunction. Methods: 64 consecutive men with Doppler proven erectile dysfunction of more than 3 months of duration were recruited. Patients divided into 2 groups according to mean peak systolic velocity (PSV). Patients with PSV <20 cm/sn constituted Group 1 and patients with PSV ≥20 cm/sn constituted Group 2. All underwent echocardiography and were compared. According to the 2D-STE analysis for the left atrium (LA); strain during ventricular systole (LARes), during late diastole (LA-Pump), strain rate during ventricular contraction (LA-SRs), during passive ventricular filling (LA-SRe), during active atrial contraction (LASRa) values and for LV; global longitudinal strain (GLS), strain rate in systole (GSRs), strain rate in early diastole (GSRe), and strain rate in late diastole (GSRa) values were obtained. Results: Beside diastolic parameters, LA-Res and LA-Pump were found to be significantly different between groups. GLS and GSR values were lower in Group 1. Moreover, correlation analysis revealed a significant correlation of GLS values with PSV (r = −0.4, P = .001). Conclusion: Myocardial deformation parameters by 2D-STE are valuable for detection of subclinical cardiovascular dysfunction in men with arteriogenic erectile dysfunction. This noninvasive method may be used as an emerging prognostic marker for risk stratification.